O Corpo como parâmetro antropológico na bioética - Reyes, Pedro Alonso Puentes (2006)
The human being as body is the central topic of this dissertation. In order to get an overview of the topic, the first part briefly discusses how the human body is dealt with in the anthropological reflections made by some philosophical and theological perspectives. The second part describes possible contributions for the definition of the human being as body. For that purpose it tries to understand the concept of soma in Paul s thinking, not by offering a direct exegesis of Paul s texts, but by refering to suggestions made by some of his interpreters. The third part undertakes an analysis of the concept of human being proposed by the biologist, Humberto Maturana. This procedure aims at elaborating on and broadening his definition that the human being is body. Then it establishes a dialogue between the views of Paul and Maturana with the purpose of delineating a concept of the human being as body. The fourth part advances some conclusions by evaluating two bioethical discourses and by sketching some implications of this anthropological definition for bioethics.